2006
DOI: 10.1016/j.brainres.2006.04.064
|View full text |Cite
|
Sign up to set email alerts
|

The development of preparation, conflict monitoring and inhibition from early childhood to young adulthood; a Go/Nogo ERP study

Abstract: The present developmental study aimed to trace changes in response expectation, preparation, conflict monitoring and subsequent response inhibition from 6 years of age to adulthood. In two groups of children (6-7 and 9-10 years old) and young adults (19-23 years old), behavior and event-related brain activity (ERP) in a CPT-AX task was measured. Hits, false alarms, inattention and impulsivity scores and ERP measures of conflict monitoring and inhibition (Nogo-N2 and P3), cue-orientation and prestimulus target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
305
8
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(383 citation statements)
references
References 50 publications
(101 reference statements)
65
305
8
5
Order By: Relevance
“…This confirms our previous finding that exogenous cognitive control is not related to antenatal maternal anxiety (Van den Bergh et al, 2005, 2006Mennes et al, 2006). Moreover, the absence of an effect of anxiety on the ERPs measured during this task strengthens this conclusion.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This confirms our previous finding that exogenous cognitive control is not related to antenatal maternal anxiety (Van den Bergh et al, 2005, 2006Mennes et al, 2006). Moreover, the absence of an effect of anxiety on the ERPs measured during this task strengthens this conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Developmental studies with visual stimuli in younger children have shown a decrease in P2a amplitude with age until adulthood (Polich, 1997;Taylor and Khan, 2000;Jonkman, 2006). The fact that the prefrontal areas of the brain undergo large developmental changes up into adolescence further supports this hypothesis (Spear, 2000;Paus, 2005).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Jonkman et al [21] found that N300 was located on both sides of the medial frontal lobe (near the ACC) of both adults and children according to the analysis of dipole sources. A localization of posterior source was required for children, and the posterior source was located in the occipital-temporal area for 6-7 years old children and in the parietal lobe for 9-10 years old children.…”
Section: Time Course Of Audio-visual Interference Inhibitionmentioning
confidence: 99%